The Stromal Vascular Fraction From Fat Tissue in the Treatment of Osteochondral Knee Defect: Case Report - Salikhov, Ramil Z.; Masgutov, Ruslan F.; Chekunov, Mikhail A.; Tazetdinova, Leysan G.; Masgutova, Galina; Teplov, Oleg V.; Galimov, Damir; Plakseichuk, Yuri; Yagudin, Ramil; Pankov, Igor O.; Rizvanov, Albert (Frontiers in Medicine, 2018)
In this study we applied autologous fat tissue stromal vascular fraction (SVF) cells in combination with microfracturing technique in a 36-year-old man with an osteochondral lesion of the medial femoral condyle 8 months after the injury. Cell material was generated by fat tissue liposuction from the anterior abdominal wall with subsequent extraction of the SVF and injected through a mini-arthrotomy portal with subsequent fibrin sealant fixation. The follow-up period was 2 years. Clinical score improved from 23 to 96 according to IKDC and from 10 to 90 according to EQ-VAS at 24 months follow-up. Magnetic resonance imaging (MRI) before the surgery revealed an osteochondral lesion with development of significant trabecular edema that remained unchanged for 6 months despite conservative treatment. MRI 1 and 2 years after the surgery showed the recovery of the damaged cartilage thickness with somewhat uneven structure and a decrease in the trabecular edema of the femoral condyle. The use of SVF cells with fibrin sealant fixation might be a promising approach in the treatment of osteochondral joint lesions. Further studies are required.